Respuesta :
Step-by-step explanation:
Add the system of equations each one by one.
I added them all downwards until i found the 4th one to be correct
y = 2x - 3
y = 2x - 3
--------------
2y = 4x - 6
y = 2x - 3.
To find the value of y in each coordinates given above, substitute their respective x values.
1......y = 2(5) - 3
= 10 - 3
= 7.
2......y = 2(8) - 3
= 16 - 3
= 13.
then write the value you substituted in x on the left side of each bracket & the value you got when you substituted them on the right.
(5 , 7) (8 , 13)